The Insanity Defence: How Do We Handle Doubt? - Rosenqvist, Randi (Bergen Journal of Criminal Law & Criminal Justice, 2019)
This paper discusses how the legal definition of criminal insanity has been altered several times in the Norwegian criminal law, most recently in June 2019. There are difficulties in communicating between psychiatric experts, legal experts, and lay judges, since the description and understanding of psychotic cognition as well as the definition of legal terms are not equally understood. Not all insanity cases are clear-cut. The Norwegian forensic experts must not conclude that the charged person is considered ‘psychotic’ in the legal sense if they are not clinically sure of this. The courts, on the other hand, must not conclude that a person is ‘sane’ if there is doubt about this. This paper discusses how there is little practical knowledge of how experts and courts handle such doubts, and highlights the lack of discussion of these questions in the legal sources.